Pengaruh Literasi Keuangan Dan Pengetahuan Akuntansi Terhadap Kinerja UMKM Di Tabanan - Padmawati, I Gusti Ayu Komang Sagung; Sumadi, Ni Komang; Padnyawati, Kadek Dewi (UNHI Press, 2025)
This study aims to examine the influence of financial literacy and accounting knowledge on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Tabanan. MSMEs play a strategic role in the economy, especially in creating jobs and improving community welfare. MSME performance reflects the level of achievement in implementing programs to realize an organization’s vision and mission. The population in this study consists of 47,957 MSMEs registered with the Tabanan Regency Cooperative and SME Trade Service. The sampling method uses incidental sampling, and based on the Slovin formula, a sample of 100 respondents was obtained. The data analysis technique used is multiple linear regression. The results show that financial literacy has a significant positive impact on MSME performance. The higher the financial literacy of business owners, the better their business performance. Accounting knowledge also has a significant positive impact on MSME performance. Increasing accounting knowledge among business owners will improve their business performance.